Menumbuhkan Bahasa Indonesia Yang Baik Dan Benar Dalam Pendidikan Dan Pengajaran - Andi Puspitasari (Fakultas Sastra - Universitas Muslim Indonesia, 2017)
Speaking is very closely related to the culture of a generation. The generation of this country is increasingly immersed in the fading of a deeper Indonesian language, maybe the Indonesian language will be increasingly staggered in shouldering its burden as a national language and national identity. In such conditions, it is necessary to provide guidance and fertilization early on to the young generation so that they do not follow the use of foreign languages. The influence of the current of globalization in national identity is reflected in the behavior of people who are starting to leave Indonesian and are accustomed to using slang. Today it is clear that in many society the use of slang and compounded by the younger generation of Indonesians who are also inseparable from the use of slang. In fact, this young generation uses the most and creates slang in the community. Another phenomenon is the language of Alay which is often used in social media and daily conversation. The shift in word structure that occurs at the present time and is carried out by many circles forms the emergence of new vocabulary that marginalizes formality in language.